Sustainable Aquaculture: Increasing Fish Productivity with Environmentally Friendly Techniques in Indonesia and Libya - Sebayang, Nico Syahputra; Baroud, Najah (CV. Bimbingan Belajar Assyfa, 2024)
Problem Statement: Sustainable aquaculture development is a global concern, especially in countries like Indonesia and Libya, which have significant potential but face environmental and social challenges. The main issue is increasing fish productivity using environmentally friendly techniques without damaging local ecosystems. Research Objective: This study aims to explore and analyze sustainable aquaculture techniques that can enhance fish productivity in Indonesia and Libya. The primary focus is techniques that minimize negative environmental impacts and understand the interaction between aquaculture and local biodiversity. Research Methodology: The study employs a systematic literature review (SLR) method to gather and analyze data from relevant previous studies. Literature from various sources, including academic journals, government reports, and local case studies, has been interpreted to gain in-depth insights into aquaculture practices in both countries. Data Analysis Techniques: Data is analyzed using a meta-analysis approach to identify common trends, the most effective techniques, and potential environmental impacts. The analysis also includes an evaluation of occupational health risks for aquaculture workers and their effect on biodiversity. Key Findings: The study reveals that aquaculture techniques such as water recirculation systems and natural feeds can significantly increase fish productivity while reducing environmental impacts. In Indonesia, community-based technologies involving local participation have shown positive results in fisheries resource management. In Libya, adapting technologies from other countries with local adjustments has demonstrated potential to improve production yields. Conclusion: Sustainable aquaculture can be achieved by applying environmentally friendly techniques and local community participation. For Indonesia and Libya, it is crucial to develop policies that support innovation in this sector while considering environmental and social impacts. Further research is needed to create more efficient and sustainable technologies and understand the complex interactions between aquaculture and local ecosystems.